Kompres Hangat Sebagai Strategi Perawatan Diri untuk Meredakan Dismenore Primer pada Remaja - Siti Sholihat; Intan Rosmita Dewi; Benny Novico Zani (JURNAL KESEHATAN REPRODUKSI, 2022)
Background: Primary dysmenorrhea is a problem that often occurs in adolescents, the incidence of dysmenorrhea is high so it is necessary for adolescents to understand how to deal with dysmenorrhea pain problems independently.Objectives: This study aims to determine the impact of warm compresses in reducing dysmenorrhea in adolescentsMethods: Pre-experimental research design with one group pretest-posttest type, on 30 female students based on inclusion and exclusion criteria. The application of warm compresses was carried out independently, previously given training on SOPs for warm compresses, paying attention to pain using the Verbal Descriptor Scale (VDS) instrument, data analysis using Wilcoxon with a significant level of 0.05.Results and Discussion: The results of the characteristic study found that respondents were at the age of 21 years, the median body mass index (BMI) was 22.2, some respondents had a menstrual period of 27.5 days with regular menstrual cycles and dysmenorrhea that occurred on the first day. The median score before intervention was 5.5 with an interquartile range (IQR) of 1.75 while the median after intervention was 0 with an IQR value of 2. The Wilcoxon test results found a significant reduction in pain before and before warm compresses with a level of 0.000 Conclusion: Compresses have a positive impact in reducing dysmenorrhea pain and can be an alternative to self-care that teenagers can do Keywords: dysmenorrhea; pain; warm compress